STARS Project lends exposure to campus life - UMP, PNC (2019)
The three-way collaborative effort between Universiti Malaysia Pahang (UMP) and selected schools and industries–dubbed Projek Kilauan Mutiara STARS, or loosely translated as the Sparkling Pearl Project (STARS) – has given the opportunities to selected secondary school students to experience life as an undergraduate on campus.